Politik dan Bencana: Kajian Rekognisi Hak Masyarakat di Pulau Terisolir di Masa Krisis - Ahmad Robi Ulzikri (Jurnal Ilmu Politik dan Studi Sosial Terapan, 2023)
This study aims to analyze how the recognition of the rights of isolated area communities, especially in the isolated islands of Sebesi Island during the crisis period after the 2018 tsunami disaster and during the COVID-19 pandemic. This study uses Axel Honnet's political recognition approach to the aspect of community rights, involving interviews with 14informants including representatives from important community figures, heads of institutions  or government who are considered competent in their fields and know the issues, documentation, and field observations. The results of the research show that the recognition of isolated island communities in the realm of society still finds denial of civil rights (securityand safety) and social rights (population, services and social assistance). This research resulted in recommendations namely the need for a settlement of land legality issues, realization of housing assistance for tsunami victims with moderate damage categories, synchronization of the Zoning Plan for Coastal Areas and Small Islands (RZWP3K) regulations and Spatial and Regional Planning regulations (RTRW) that accommodate rights the people of Sebesi Island.